Saint Augustin - Bertrand, Louis, 1866-1941; O'Sullivan, Vincent, 1868-1940 (Salt Lake City, UT : Project Gutenberg, 2005)
"Saint Augustin" by Louis Bertrand is a biographical account written in the early 20th century. The book explores the life and legacy of Saint Augustine of Thagaste, a pivotal figure in Christian theology whose thoughts and writings have shaped Western philosophy and Christianity. It delves into his early life, upbringing, and the formative experiences that influenced his journey from a pleasure-seeking youth to a revered bishop and theologian. The opening of the work begins with a prologue that reflects on the contemporary neglect of Saint Augustine's work outside of academic circles, emphasizing the complexities and richness of his life. It describes his origins in Thagaste, highlighting the picturesque environment of his childhood and the contrasting social dynamics of his family, particularly the influence of his Christian mother, Monica. As the narrative unfolds, readers witness the initial stages of Augustine's life marked by youthful playfulness, curiosity, and the early stirrings of rebellion against traditional morals, setting the stage for his later profound struggles with faith and identity. (This is an automatically generated summary.)
Release date is 2005-10-01
Produced by Charles Aldorondo, Tiffany Vergon, William Flis, and Distributed Proofreaders
Keywords: Augustine, of Hippo, Saint, 354-430; Christian saints -- Algeria -- Hippo (Extinct city) -- Biography